2019
DOI: 10.1097/cm9.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Application and prospects of butylphthalide for the treatment of neurologic diseases

Abstract: Objective The 3- N -butylphthalide (NBP) comprises one of the chemical constituents of celery oil. It has a series of pharmacologic mechanisms including reconstructing microcirculation, protecting mitochondrial function, inhibiting oxidative stress, inhibiting neuronal apoptosis, etc. Based on the complex multi-targets of pharmacologic mechanisms of NBP, the clinical application of NBP is increasing and more clinical researches and animal experiments are also focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 82 publications
0
47
0
Order By: Relevance
“…Other molecules, which are not specific for the treatment of neurodegenerative diseases, can counteract mitochondrial alterations, preventing a wide range of altered mechanisms. For instance, 3-N-butylphthalide (NBP), a compound widely employed in the treatment of ischemic stroke in China thanks to its ability in restoring microcirculation [227], can (i) maintain mitochondria permeability and dynamics (preventing mitochondria swelling), (ii) improve mitochondria bioenergetics (increasing complex IV activity), (iii) prevent cytochrome c release and caspase-dependent apoptosis, and (iv) counteract ROS production. Indeed, most of these effects have been observed on in vitro and in vivo PD models, determining neuroprotection and behavioral improvement [228,229] and a randomized controlled trial has demonstrated NBP efficacy in improving motor symptom and sleep quality of PD patients [230].…”
Section: Compounds Targeting Multiple Mitochondrial Dysfunctionsmentioning
confidence: 99%
“…Other molecules, which are not specific for the treatment of neurodegenerative diseases, can counteract mitochondrial alterations, preventing a wide range of altered mechanisms. For instance, 3-N-butylphthalide (NBP), a compound widely employed in the treatment of ischemic stroke in China thanks to its ability in restoring microcirculation [227], can (i) maintain mitochondria permeability and dynamics (preventing mitochondria swelling), (ii) improve mitochondria bioenergetics (increasing complex IV activity), (iii) prevent cytochrome c release and caspase-dependent apoptosis, and (iv) counteract ROS production. Indeed, most of these effects have been observed on in vitro and in vivo PD models, determining neuroprotection and behavioral improvement [228,229] and a randomized controlled trial has demonstrated NBP efficacy in improving motor symptom and sleep quality of PD patients [230].…”
Section: Compounds Targeting Multiple Mitochondrial Dysfunctionsmentioning
confidence: 99%
“…Previous studies indicated that dl-3-N-butylphthalide (NBP) not only improved neurological function, but also contributed to the long-term outcomes. [ 13 ] The mechanisms of NBP for ischemic stroke treatment may involve many complex molecular mechanisms, including anti-oxidant, anti-thrombosis, anti-apoptosis, anti-inflammation, protection of mitochondria, and so on. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Butylphthalide was first extracted from the celery seed and was discovered within the last few decades. [ 10 ] The main pharmacologic effects of butylphthalide include antiplatelet aggregation effect, mitochondria protect effect, antiapoptotic effect, and so on. [ 11 14 ] Based on the therapeutic property of this compound, butylphthalide was artificially synthesized later in China and approved by the China Food and Drug Administration for ischemic stroke and neuro impairment induced by ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 14 ] Based on the therapeutic property of this compound, butylphthalide was artificially synthesized later in China and approved by the China Food and Drug Administration for ischemic stroke and neuro impairment induced by ischemic stroke. [ 10 ] Due to its promising pharmacological effect and good safety profile, butylphthalide is widely used as an adjunctive therapy for ischemic stroke. [ 15 ] It is also used for neurodegenerative diseases such as Alzheimer disease and Parkinson disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation